Degradation of Cellulose Acetate in Simulated Aqueous Environments: One‐Year Study. Issue 6 (9th February 2022) - Yadav, Nisha; Hakkarainen, Minna
Abstract: Cellulose acetate (CA) is subjected to different aqueous environments (e.g., lake water, seawater, artificial seawater) under controlled laboratory conditions to investigate the degradation potential in natural water systems. The main changes in the CA films are detected during the first months of the 12‐month study. Approximately 5% and 10% weight losses are observed during the first month of aging at RT and at 60 °C, respectively. The temperature effect is rather negligible and the weight loss also does not significantly increase on prolonged aging. A quantitative high‐performance liquid chromatography analysis shows that this weight loss is mainly caused by deacetylation and depending on the aging conditions, 10–30% of the acetate groups are lost during the first 1–3 months of aging. Fourier transform infrared and nuclear magnetic resonance analyses further support this. It is well established that a high degree of substitution (DS) is the bottleneck for biodegradation of CA and a significantly higher biodegradation rate has been demonstrated for CA materials with degree of substitution, DS<2, compared to those with DS>2. The degree of deacetylation observed here is enough to decrease the DS to below 2, which can therefore have a significant effect on the subsequent biodegradation. Abstract : The degradation of cellulose acetate in different aqueous environments, such as seawater, lake water, and artificial seawater, is evaluated under controlled laboratory conditions. The main degradation process observed is deacetylation. Although the overall degree of degradation is limited, the observed deacetylation can be enough to significantly enhance the biodegradability of the remaining cellulose acetate films.